The Prognostic Model Based on Tumor Cell Evolution Trajectory Reveals a Different Risk Group of Hepatocellular Carcinoma - Wang, Haoren; Yu, Shizhe; Cai, Qiang; Ma, Duo; Yang, Lingpeng; Zhao, Jian; Jiang, Long; Zhang, Xinyi; Yu, Zhiyong (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) is the fourth cause of cancer-related mortality worldwide and the major barrier to improve patient outcome is the heterogeneity of HCC. Here, we performed the analysis of transcriptomic of HCC on single cell resolution to reconstructed the malignant progression trajectory. Based on the degree of DNA copy number aberrations, we identified two distinct states of malignant cells. Trajectory analysis suggested that low-malignant sub-clone have tendency to progress to high-malignant sub-clone. Next, the single cell level and bulk level transcriptome data were combined to establish a prognostic model. C-index and ROC curve indicated that the model had excellent predictive value for HCC. Downstream analysis suggested that the bulk level data exhibited high concordance with single-cell level data in molecular and functional characteristics, including genomic instability and progression-related features. In summary, we established a novel prognostic model base on tumor cell progression trajectory to distinguish different risk groups in HCC, providing possibility of stratified medicine for HCC patients and then improving their survival outcomes.